Bioactive adrenomedullin in sepsis patients in the emergency department is associated with mortality, organ failure and admission to intensive care. - Oscar H M Lundberg; Mari Rosenqvist; Kevin Bronton; Janin Schulte; Hans Friberg; Olle Melander (PLoS ONE)
Background Adrenomedullin is a vasoactive hormone with potentially prognostic and therapeutic value, which mainly has been investigated in intensive care unit (ICU) settings. The triaging in the emergency department (ED) of patients to the right level of care is crucial for patient outcome. Objectives The primary aim of this study was to investigate the association of bioactive adrenomedullin (bio-ADM) with mortality among sepsis patients in the ED. Secondary aims were to investigate the association of bio-ADM with multiple organ failure (MOF), ICU admission and ED discharge. Methods In this prospective observational cohort study, adult sepsis patients in the ED (2013-2015) had blood samples collected for later batch analysis of bio-ADM. Odds ratios (OR) with 95% confidence interval (CI) for bio-ADM were calculated. Results Bio-ADM in 594 sepsis patients was analyzed of whom 51 died within 28 days (8.6%), 34 developed severe MOF, 27 were ICU admitted and 67 were discharged from the ED. The median (interquartile range) bio-ADM was 36 (26-56) and 63 (42-132) pg/mL among survivors and non-survivors, respectively, 81 (56-156) pg/mL for patients with severe MOF and 77 (42-133) pg/mL for ICU admitted patients. Each log-2 increment of bio-ADM conferred an OR of 2.30 (95% CI 1.74-3.04) for mortality, the adjusted OR was 2.39 (95% CI 1.69-3.39). The area under the receiver operating characteristic curve of a prognostic mortality model based on demographics and biomarkers increased from 0.80 to 0.86 (p = 0.02) when bio-ADM was added. Increasing bio-ADM was associated with severe MOF, ICU admission and ED discharge with adjusted ORs of 3.30 (95% CI 2.13-5.11), 1.75 (95% CI 1.11-2.77) and 0.46 (95% CI 0.32-0.68), respectively. Conclusion Bio-ADM in sepsis patients in the ED is associated with mortality, severe MOF, ICU admission and ED discharge, and may be of clinical importance for triage of sepsis patients in the ED.